SWOC Analysis on CCS: A Case for Oxy-fuel Combustion CO2 Capture System - Han, M.Y.; Yang, Q.; Wu, X.D.; Wu, T.H.; Chen, G.Q. (Journal of Environmental Accounting and Management, 2026)
Carbon capture and storage (CCS) has drawn worldwide attentions as a low-carbon technology alternative. Though China is deemed as a key player in the global context to slash CO2, the future of CCS in China is still highly uncertain. This study presents an overview for CCS development in China and gives detailed analyses on strengths, weaknesses, opportunities and constraints (SWOC) on CCS. Taking oxy-fuel combustion CO2 capture system as a case in this study, much of the uncertainties rest in the lack of clarity about the technical mechanisms and high costs in air separation unit (ASU), given the fact that small-scale post-combustion and pre-combustion capture systems have been applied in industrial processes. Under such cir- cumstances, high costs, immature technologies, lack of regulatory framework, and insufficiency of international collaboration are identi-fied as the major factors affecting the development of CCS in China. Extensive attentions should be focused on these aspects, in particular the high costs and immature technologies coupled with CO2 capture.